Technical dynamic capabilities in the opinion of Polish producers from the agricultural machines sector = Techniczne zdolności dynamiczne w opinii polskich wytwórców sektora maszyn rolniczych - Nogalski, Bogdan; Niewiadomski, Przemysław; Szpitter, Agnieszka A. (Zielona Góra: Faculty of Economics and Management Press)
The main aim of this paper is to develop a model of key technical dynamic capabilities providing implementation flexibility of manufacturing companies of the Polish agricultural sector. Achieving the main target required to formulate sub-targets, to which the following have been included: the query of subject literature remaining in a direct relation to the topic of the research, which, in the authors' intention, will find its expression in the developed definition of technical dynamic capabilities.
Keywords: techniczne zdolności dynamiczne; elastyczność implementacyjna; sektor maszyn rolniczych; opinie wytwórców; okazja; szansa; technical dynamic capabilities; implementation flexibility; agricultural machinery sector; opinion of producers; opportunity; chance